(untitled) (Revista de Ciências Agroveterinárias, 2006)
This paper presents aspects about forest biodiversity, your importance for sustainable management to obtain medicinal plants, included traditional knowledge and local communities participation to purpose strategies for management. Drimys brasiliensis is used like a example of researches produced by Núcleo de Pesquisas em Florestas Tropicais from Universidade Federal de Santa Catarina.